Applying the World-System theory in the conservation sciences to understand COVID-19 pandemic as a socio-environmental synergy - Hirschfeld, María Noel; R Faria, Luiz Roberto; Gil, Gabriel de Siqueira; Fonseca, Carlos Roberto (Ethnobiology and Conservation, 2023)
The pandemic of COVID-19 caused a global epidemiological, economic and social crisis. In the conservation sciences, several studies have focused efforts on understanding the effects of declining human activities on biodiversity, understanding the pandemic as an anthropogenic "pause"of global scale. But the impact of the pandemic was not the same for everyone. Different impacts are consequences of political and ethical questions about who and what can pause or be paused, according to what authority and under what conditions. Therefore, the historical asymmetrical relations of power in the World System are crucial to understanding environmental impacts and thinking about solutions in the post-pandemic world. This article discusses why historical local-global inequalities should be an indispensable reference variable for examining the different experiences caused by the pandemic in biodiversity, aiming at advancing the discussion about the society-nature relationship that the pandemic has spurred. To do so, we use the World-System Theory, initially proposed by Wallerstein, whose analytical categories allow us to situate nature conservation within broader economic, historical, and contemporary contexts. We argue for the understanding of biodiversity conservation in the context of the historical-sociological and global-local relations of the World-System. Finally, we discuss that the COVID-19 pandemic should be understood as an emergent phenomenon of the society-nature dynamic of the world-system.